Pushing Pose Sensing of Underground Mobile Supporting Robot. (8th June 2022) - Wang, Nan; Liu, Hao; Li, Xiaobiao; Tian, Meizi; Zhang, Lin
Abstract : The pushing pose of underground mobile supporting robot (MSR), i.e., hydraulic support, is a key factor to measure the straightness of the working face. Therefore, in order to independently complete the pushing process and ensure the straightness requirements of the pushing pose, by considering the pushing displacement of MSR and the pose of the middle groove of the scraper conveyor, this study proposes a fusion evaluation model combined with the least square straightness based on the pushing displacement and the straightness based on the pose of the middle groove. The pose sensing approach is established by estimating the pose of the middle groove and the displacement of MSR, analyzing, and extracting the data characteristics of acceleration signal; the OVR (one-versus-rest) method is used to realize the displacement state pattern recognition of hydraulic support based on SVM (support vector machine). The effectiveness of this approach is verified by building an experimental platform.